De L’Histoire véritable au boulet de Jules Verne : une histoire science-fictionnelle des paradigmes astronomiques - Estelle Blanquet; Éric Picholle (ReS Futurae)
The golden legend of modern astronomy often reduces its history to two defining moments : the ‘Copernican revolution’ and Galileo’s challenge to the presumed obscurantism of the Church. Inevitably, its real history is richer and more subtle, in constant interaction with the scientific imagination of its time. We propose to reread it in the light of the history of science fiction, to examine how the latter may have contributed to destabilizing the astronomical paradigms of the past ; we will also attempt to identify some of the didactic issues associated with these conceptual changes. SF authors offer those who know how to spot them situations that make it easier for students to identify choices linked to paradigmatic simplifications that have never been questioned ; it’s then up to the teacher to build a system that enables them to better understand these choices, so as to overcome arguments of authority and better accept the proposed paradigm shifts. We’ll begin by identifying a number of classic as well as less-known SF works whose potential for destabilizing astronomical paradigms can be exploited in the classroom. We’ll then show how similar processes are at work in science fiction images, such as Manchu’s « Framed Earth », and illustrate how these works can be used in the case of astronomical paradigms, using a few examples of investigative sequences.